1997
DOI: 10.1007/bf03403896
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intakes of Senior Women: Balancing the Low-Fat Message

Abstract: Older people may be at increased risk nutritionally because of chronic medical conditions, disability and/or physiological changes that interfere with consumption, absorption or metabolism of nutrients. 1 A number of Canadian dietary studies have identified low intakes of energy, zinc, calcium, Vitamin D and folate as potential problems in elderly women living independently. 2-9 Reduced consumption of red meat and dairy products-excellent sources of protein, zinc, calcium, and Vitamin Din response to nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…One mission for nurses is to ensure a high quality of the last years of a person's life. The health message of today, including a low-fat diet (Bogan 1997) and the need for women to be slim, does not suit healthy or frail older women. Here, health promotion needs to be differentiated.…”
Section: Discussionmentioning
confidence: 99%
“…One mission for nurses is to ensure a high quality of the last years of a person's life. The health message of today, including a low-fat diet (Bogan 1997) and the need for women to be slim, does not suit healthy or frail older women. Here, health promotion needs to be differentiated.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, inadequacy of dietary intake seems common in seniors in both developing and developed countries. Inadequate dietary intakes of energy, folate, vitamin D, vitamin B-6, calcium and zinc have been reported in elderly people over 60 years old [ 24 - 26 ]. For example, recent studies suggested that more than a half of elderly Americans (≥71 years) had inadequate intakes of vitamin A and E, and over one quarter of US seniors’ intakes of vitamin B12, C, D and K, folate were below EAR [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%